Komunikasi Interpersonal Shadow Teacher dalam Membangun Kepercayaan Diri Anak Berkebutuhan Khusus - Falihah, Qoni’atul (Dimar Jaya Publishing, 2024)
This study aims to describe the role of interpersonal communication carried out by shadow teachers in building the self-confidence of children with special needs at Sekolah Kreatif SD Muhammadiyah 20 Surabaya. The approach used in this study is qualitative with a case study method. Data collection techniques were carried out through observation, in-depth interviews, and documentation. The results of the study indicate that interpersonal communication between shadow teachers and children with special needs, including empathy, openness, supportive attitudes, and physical and emotional presence, contributes to increasing children's self-confidence. In addition, relationships built on trust and acceptance can create a safe and comfortable learning environment for children to develop optimally. These findings emphasize the importance of training and mentoring for shadow teachers in developing interpersonal communication skills that are responsive to the individual needs of children.